RELASI ANTARA METAFORA PERCINTAAN PERIODE PASCAPERANG DENGAN KARYA SASTRA REALISME ROMANTIK DALAM KARYA NIKOLAI GRIBACHOV DAN UTUY TATANG SONTANI - Aldrie Alman Drajat; Langgeng Prima Anggradinata (Universitas Pakuan, 2021)
Abstract War creates a bitter experience for human life. In fact, that bitter experience lasted until the war ended. This is represented through postwar literary works. This article aims to analyze the metaphors of postwar period romance in two literary works, Gribachov's